NEW EPIGRAPHY FROM THE ASSUMPTION CATHEDRAL OF ANCIENT HALYCH - HUSAK, Andrii; KREKHOVETSKYI, Ihor; LUKOMSKYI, Yurii (Halych. Scientific work collection, 2023)
11 epigraphic depictions of crosses are introduced into scholarly circulation which were discovered on the front surface of a reused alabaster block during the archaeological excavation of one of the windows of the Viizdova Tower of the second half of the 16th century of Starostynskyi Castle in Halych above the Dnister river. The block and drawings on it come from the Assumption Cathedral of the second half of the 12th – third quarter of the 16th century of princely Halych – Krylos. After a brief description of the immovable artifacts, historical stone processing technologies are analyzed, the most likely original application site of the block is determined, questions of dissemination routes, traditions of use, typological, technological, and other features of the monuments are considered, as well as the chronology and possible reasons for their appearance.